Everyday Tolerance under Syariat Islam: Muslim Perceptions of Chithirai Maha Puja in Banda Aceh - Yusuf, Bukhari; Azman, Zakirah; Nurdin, Ibnu Phonna; Susarno, Andri; Fatia, Dara (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
In Banda Aceh, the public celebration of Chithirai Maha Puja by the Hindu Tamil community takes place within a Muslim-majority city formally shaped by Syariat Islam, or Islamic sharia. This article asks how Muslim residents in Gampong Keudah make sense of this visible minority ritual and how their interpretations shape local religious coexistence. Drawing on Alfred Schutz’s phenomenology, the study uses in-depth interviews, observation, and documentation with seven Muslim informants living around Kuil Palani Andawer, or Palani Andawer Temple. The analysis identifies three patterns of perception. Some residents support the celebration through practical assistance, including food preparation, parking, and public order. Others regard it as an ordinary part of neighborhood life that does not disturb Muslim worship or daily routines. A third group expresses concern about the visibility of Hindu ritual symbols, especially in relation to children’s religious education. These findings show that tolerance in Gampong Keudah is not a simple matter of acceptance or rejection. It is practiced through familiar neighborhood relations, practical coordination, symbolic adjustment, and the careful maintenance of religious boundaries. The article argues that Chithirai Maha Puja remains socially intelligible in Banda Aceh because it is embedded in long-term proximity, Acehnese moral vocabularies, and shared knowledge about how minority ritual expression can occupy public space without openly challenging Muslim-majority sensibilities.